Advantages of binary stochastic synapses for hardware spiking neural networks with realistic memristors. Issue 3 (1st September 2022) - Sulinskas, Karolis; Borg, Mattias
Abstract: Hardware implementing spiking neural networks (SNNs) has the potential to provide transformative gains in energy efficiency and throughput for energy-restricted machine-learning tasks. This is enabled by large arrays of memristive synapse devices that can be realized by various emerging memory technologies. But in practice, the performance of such hardware is limited by non-ideal features of the memristor devices such as nonlinear and asymmetric state updates, limited bit-resolution, limited cycling endurance and device noise. Here we investigate how stochastic switching in binary synapses can provide advantages compared with realistic analog memristors when using unsupervised training of SNNs via spike timing-dependent plasticity. We find that the performance of binary stochastic SNNs is similar to or even better than analog deterministic SNNs when one considers memristors with realistic bit-resolution as well in situations with considerable cycle-to-cycle noise. Furthermore, binary stochastic SNNs require many fewer weight updates to train, leading to superior utilization of the limited endurance in realistic memristive devices.